On inferred real-world fuel consumption of past decade plug-in hybrid electric vehicles in the US. (1st October 2022) - Hamza, Karim; Laberteaux, Kenneth P; Chu, Kang-Ching
Abstract: Plug-in hybrid electric vehicles (PHEVs) have powertrain architectures that seek to combine the best features of two well-known powertrains: the environmental and other benefits of electric driving of battery electric vehicles; and the fuel efficiency and, due to widely-available fueling infrastructure and quick refueling times, limitless practical range of hybrid electric vehicles (HEVs). Different regulatory organizations around the world have different standard testing procedures, and accordingly, different predictions for the degree of efficacy of PHEVs at reducing greenhouse gas (GHG) emissions. However, there is somewhat of a consensus that PHEVs have the capacity for significant GHG reduction compared to conventional internal combustion engine vehicles, yet some recent studies have claimed the real-world fuel consumption of PHEVs to be more than twice their standard ratings. A key factor to the efficacy of GHG reduction via PHEVs is the fraction of miles traveled in electric mode, also known as the utility factor (UF). In this work, we reinvestigate the data sources cited in previous studies for PHEVs in the US for the inferred real-world UF and fuel consumption via same estimation approaches as a previous study. We then compare with UF from SAE J2841 standard and fuel consumption ratings from the US environmental protection agency. While noting that it is difficult if not impossible to discern the exact reason for observed deviations given the available information in the cited data sources, we find the real-world fuel consumption of PHEVs in the US to be within 62% better to 21% worse than their standard ratings in the US, and generally, significantly better than a comparable HEV. Contrasted with reported results for other parts of the world, the results are viewed as a testimony to the importance of proper procedures for evaluation of PHEVs to reflect their correct environmental benefit value.